Heritage-specific oral microbiota in Indigenous Australian dental calculus. Issue 1 (5th August 2022) - Handsley-Davis, Matilda; Kapellas, Kostas; Jamieson, Lisa M; Hedges, Joanne; Skelly, Emily; Kaidonis, John; Anastassiadis, Poppy; Weyrich, Laura S
Abstract: Background and objectives: Aboriginal Australians and Torres Strait Islanders (hereafter respectfully referred to as Indigenous Australians) experience a high burden of chronic non-communicable diseases (NCDs). Increased NCD risk is linked to oral diseases mediated by the oral microbiota, a microbial community influenced by both vertical transmission and lifestyle factors. As an initial step towards understanding the oral microbiota as a factor in Indigenous health, we present the first investigation of oral microbiota in Indigenous Australian adults. Methodology: Dental calculus samples from Indigenous Australians with periodontal disease (PD; n  = 13) and non-Indigenous individuals both with ( n  = 19) and without PD ( n  = 20) were characterized using 16S ribosomal RNA gene amplicon sequencing. Alpha and beta diversity, differentially abundant microbial taxa and taxa unique to different participant groups were analysed using QIIME2. Results: Samples from Indigenous Australians were more phylogenetically diverse (Kruskal–Wallis H  = 19.86, P  = 8.3 × 10 −6 ), differed significantly in composition from non-Indigenous samples (PERMANOVA pseudo- F  = 10.42, P  = 0.001) and contained a relatively high proportion of unique taxa not previously reported in the human oral microbiota (e.g. Endomicrobia). These patterns were robust to stratification by PD status. Oral microbiota diversity and composition also differed between Indigenous individuals living in different geographic regions. Conclusions and implications: Indigenous Australians may harbour unique oral microbiota shaped by their long relationships with Country (ancestral homelands). Our findings have implications for understanding the origins of oral and systemic NCDs and for the inclusion of Indigenous peoples in microbiota research, highlighting the microbiota as a novel field of enquiry to improve Indigenous health. Lay Summary: The community of microorganisms in the mouth (oral microbiota) has recently been linked to several chronic diseases that disproportionately impact Indigenous Australians. In this study, oral microbiota differ significantly between Indigenous Australians and non-Indigenous counterparts, suggesting the microbiota could be a novel factor with the potential to improve Indigenous health outcomes.